Dwie wersje Modlitwy Pańskiej odczytane w kluczu inicjacyjnym - Mateja, Leszek (Vox Patrum, 2018)
The article attempts to prove the validity of Origen’s thesis that two versions of the Lord’s Prayer noted by evangelists Matthew and Luke represents two different prayers. To validate the thesis, the author interprets extracts from the New Testament by using the initiation method. Through this method he demonstrates that catechumens were probably taught the version of the Lord’s Prayer noted by Luke, while the version written by Mark could be destined for those who had been baptised.